2022
DOI: 10.1111/hsc.13875
|View full text |Cite
|
Sign up to set email alerts
|

Using the Revised Health Care System Distrust Scale to evaluate healthcare distrust among Chinese men in Hong Kong: An analysis from a prostate cancer screening behaviours survey

Abstract: Information about the level of distrust in healthcare systems is very limited in Chinese populations, and no validated instrument has been developed to measure this distrust. Therefore, to begin addressing this research gap, this study evaluated the psychometric properties of a traditional Chinese version of the Revised Health Care System Distrust Scale and used it to assess the level of distrust in a healthcare system. The study involved a community-based personal interview survey of individuals in Hong Kong.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Short-form videos have become invaluable in disseminating health information [15], especially with an uptick in usage among the elderly on platforms like TikTok [16]. These videos are crucial for medical education due to their accessibility and ease of understanding [17].…”
Section: Medical Communications and Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-form videos have become invaluable in disseminating health information [15], especially with an uptick in usage among the elderly on platforms like TikTok [16]. These videos are crucial for medical education due to their accessibility and ease of understanding [17].…”
Section: Medical Communications and Technologiesmentioning
confidence: 99%
“…Previous research has explored the effectiveness of medical short-form videos. For instance, Rong et al assessed videos related to Chronic Obstructive Pulmonary Disease (COPD) and found the overall quality of these videos satisfactory, although patients still need to exercise discretion in filtering information [15]. Another study demonstrated that hypertensive patients benefited from watching videos about healthy lifestyles, underscoring the potential of medical content videos as auxiliary tools for treatment [18].…”
Section: Medical Communications and Technologiesmentioning
confidence: 99%